Mapping structural lineaments using the edge filters of the potential field: a case study of the Rizhao–Lianyungang area, East China - Sun, Yanyun; Zeng, Xiangzhi; Yang, Wencai; Li, Xiao; Zhang, Wan; Zhang, Xuanjie (Frontiers in Earth Science, 2023)
Background: Edge enhancement plays an important role in potential field data processing and interpretation, which facilitate regional tectonic studies, mineral and energy exploration. This is because edges on potential field often indicate linear geological structures such as fractures, edges of geological bodies and so on. With the development of meticulous edge enhancement on potential field, the phenomenon of false edges caused by the associated anomalies when detect ing edges from magnetic field cannot be ignored. Methods: Aiming at this problem, we proposes a modified magnetic edge detection method (SP Mag) based on the second order spectral moment. This method has been tested on both synthetic and field data. The synthetic test show that SP Mag cannot only balanced edges no matter from strong or weak anomalies, but also eliminates those false edges caused by the associated anomalies in magnetic field, which provide more effective information for subsequent interpretation. Results: We apply this new method to the RTP aero magnetic field and gravity field of Rizhao Lianyungang area. The lineaments recognized by the SP Mag method correspond well with geologic structures through comparing with geological maps. Discussion: The results illustrate the usefulness of the method for potential field interpretation. Furthermore, more geological and geophysical data should be still combined for comprehensive interpretation in the actual interpretation, though the SP Mag method can recognize lineaments effectively.